The Urgency of Sharia Notarial Practice in Indonesia: Islamic Law Critique of Law No. 2 of 2014 on Notary Position and Its Contribution to Sharia Economic Law - Ustad Adil; Ija Suntana; Siah Khosyi'ah; Uu Nurul Huda (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
This study aims to explore the urgency of Sharia notary law in Indonesia, as well as critique Islamic law regarding Law No. 2 of 2014 concerning the Notary Public and its contribution to Sharia economic law. This research method uses a descriptive analytical approach with a normative juridical approach by analyzing applicable laws and regulations and relevant Islamic legal principles. The results indicate that Law No. 2 of 2014 does not fully accommodate provisions regarding notary law in the context of Sharia economic transactions, such as Sharia contracts, which must be fair and certain. This points to the urgent need to integrate elements of Islamic law into notary law to provide greater legal certainty for Sharia economic transactions. This study also reveals the importance of Sharia notary law from a philosophical, juridical, sociological, and practical perspective. This study then recommends that the Notary Law be revised to incorporate provisions in accordance with Sharia principles, thereby strengthening the legal infrastructure of Sharia economics in Indonesia.